Effects of Indigenous Saudi Herbals on Weight Control in High Fat Diet-fed STZ Induced Diabetic Rats - Sangi, Sibghatullah; AlOtaibi, Nawaf M.; Bawadekji, Abdulhakim; Soomro, Samreen (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Introduction: Obesity, a critical global issue, involves the accumulation of excessive body fat, elevating the risk of diabetes, hypertension, and other severe health conditions. This widespread concern is particularly pronounced in nations like Saudi Arabia, demanding urgent and efficient management approaches. Addressing weight control necessitates comprehensive interventions encompassing education, dietary modifications, and increased physical activity. By following healthier lifestyles and fostering a supportive environment, improvement can be made on healthcare systems. Collaboration between governments, healthcare professionals, and communities is pivotal to reduce obesity's impact and fostering a healthier generations. Methods: Research Design and Objectives: This study aimed to fill the existing void in excessive body weight treatments by investigating viable herbal interventions that are safe, readily accessible, and economically viable. Wistar albino rats were grouped to 5 groups with 5 animals each. Diabetics were induced by intraperitoneal injection of streptozotocin for all groups except group 1. Then respective groups were fed with fat diets for 12 weeks and herbals Zingiber officinale (ginger), Nigella sativa (black seeds) and Allium sativum (Garlic) from 7th to 12th weeks along with high fat diet. Mean Body weight and Lee's obesity index were calculated for each group. Results and Discussion: In the realm of herbal efficacy, a striking trend surfaces. Among the diverse materials scrutinized, one distinct name rises—Garlic (Allium sativum). Its prowess in diminishing both body weight and fat content stands out prominently. Across the tested spectrum, a consistent and impressive reduction in weight prevails. Particularly, Garlic asserts its dominance as a singularly remarkable performer, showcasing unparalleled effectiveness. This herbal gem not only underscores its potency but also solidifies its position as a preeminent agent for weight and fat reduction. The findings unequivocally spotlight Garlic's exceptional role in promoting healthier body composition. Conclusions: Herbals as Adjunctive Therapy for Obesity The findings underscore the potential of herbal interventions, particularly Garlic, in the management of weight control. These natural remedies hold promise as adjunctive therapeutic agents. However, further rigorous human trials and animal studies with large sample size and different methodology are essential to validate their efficacy and integration into obesity / weight control treatment regimens.